2019
DOI: 10.1186/s12879-018-3668-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and viral etiologies of outpatients with acute respiratory infections in Huzhou of China: a retrospective study

Abstract: BackgroundViruses are commonly found in patients with acute respiratory infections (ARIs). However, the viral etiologies and clinical characteristics of outpatients with ARIs are poorly understood in China. Here, we identified the viral etiologies in outpatients with ARIs in Huzhou, China.ResultsOur results indicated that of 426 outpatients, 246 were positive for viruses. Of them, 221 were positive for a single virus, including influenza A, which comprised H3N2 (28.5%) and pandemic H1N1 (2009) (19.0%), enterov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
2
10
0
1
Order By: Relevance
“…Wang H, et al had reported the nearly result in Shenzhen [16], but it was lower than in 22 provinces of China (36.6%) and Shandong (35.75%) [7,13]. The overall infection rate decreased with the increase of children's age, these results suggested that pathogens in ARIs were closely associated with patient's age which affects exposure opportunities to viruses and immune status, the result is consistent with the previous report [18]. The single infection rate in infants is as high as 18.84%.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Wang H, et al had reported the nearly result in Shenzhen [16], but it was lower than in 22 provinces of China (36.6%) and Shandong (35.75%) [7,13]. The overall infection rate decreased with the increase of children's age, these results suggested that pathogens in ARIs were closely associated with patient's age which affects exposure opportunities to viruses and immune status, the result is consistent with the previous report [18]. The single infection rate in infants is as high as 18.84%.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, respiratory pathogen infections had major seasonal changes, most of which occurred in the winter and were lowest in the spring. Similar results were reported in other studies [18,32], which is different from Shenzhen and Shandong [2,7]. The difference in seasonal pathogen detection is affected by a variety of factors, among which climate is an important factor, such as the time of sunlight exposure, temperature, humidity and so on, which change the duration of the virus in the environment [33].…”
Section: Discussionsupporting
confidence: 83%
“…Presently, several diagnostic methods for the detection of respiratory virus, including virus culture, viral‐antigen detection, and viral‐antibody detection have been described . Virus culture is a gold standard method; however, this method is labor‐intensive and time‐consuming, making it impractical to be used in the clinical laboratory .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that ARTI prevalence in children may vary in different geographic regions and different seasons . However, information regarding viral ARTI in pediatric hospitalized children in Fuzhou city (central Fujian) is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…. При этом тяжелое осложненное течение, необходимость госпитализаций и неблагоприятный прогноз ОРВИ характерны для ко-инфекций, больше распространенных среди пожилых и детей младшего возраста, а также для пациентов, зараженных вирусом иммунодефицита человека либо имеющих соматические факторы риска [13,[15][16][17]. К последним можно отнести не только хронические заболевания дыхательных путей, включая бронхиальную астму, но и хронические заболевания сердечно-сосудистой системы, а также сахарный диабет (СД), распространенность которого в мире постоянно увеличивается.…”
unclassified